Pengaruh Metode Pembelajaran Bermain Peran Terhadap Kemampuan Berbahasa Pada Anak Kelas 2 SD Negeri 060826 Kec. Medan Area - Rizka Fadhilah Priono; Juni Mellyani Hasibuan; Zulhijjah Febriyani Sitepu; Syahrial Syahrial (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to find out how role-playing games can be used to support language development in children aged 6 to 7 years. The research method used is an experimental method, where the population in this research is all second grade elementary school students. The technique used in this research is by Using observation and data collection techniques using role-playing questionnaires was very effective and efficient in class II elementary school because from the results of planning, implementation and observation, success reached 90%, that role-playing can improve students' vocabulary, communication and linguistics